Human dignity the basis of the right to religious freedom - WROCEŃSKI, JÓZEF (Prawo Kanoniczne, 2017)
In his paper the author reflects on human dignity in the context of the right to religious freedom. First, he analyses the concept of fundamental human rights reaching back to ancient times, and then he discusses the concept of human dignity. He presents the concept of dignity in the teaching of the Catholic Church and in documents of secular law, among others, in the documents of international law, European law, the Polish Concordat, and the Polish Constitution. The author argues that inherent human dignity is the basis to guarantee freedom of conscience and religion. For that reason neither the State nor the churches, including the Catholic Church, can restrict this freedom, because it does not come from them.